All-pass Filter Application Using Electronically Tunable DDCC - (:unkn) unknown (IEEE, 2014)
In this study, an electronically tunable differential difference current conveyor is presented. The benefits of this new active element are demonstrated on tunable first-order voltage-mode all-pass filter employing a resistor and a capacitor. In the proposed filter structure using single active and two passive elements no element-matching restriction is required. The theoretical results are verified with SPICE simulations using TSMC 0.35 mu m CMOS process parameters and with +/- 2.5 V supply voltages.
Keywords: analog filters; all-pass; current conveyor; first-order; electronically tunable differential difference current conveyor; E-DDCC; voltage-mode; CURRENT CONVEYORS; ALLPASS FILTER; SINGLE CCII; RESISTORS; SECTION; CAPACITORS